The Post-Institutional Treatment of Convicts - Ilijić, Ljeposava; Maljković, Marija (Zbornik Instituta za kriminološka i sociološka istraživanja, 2015)
Post-institutional treatment, as the last stage in the process of reintegration of convicts, in our practice has been long neglected, primarily because of the underdeveloped system of post-institutional assistance. That situation compromised the modest results of custodial treatment. This is best evidenced by the high rate of recidivism, which in our institutions ranges of 60–70%. In recent years, Serbia has made a major breakthrough in this area by adopting a series of laws, and of particular importance is the establishment of a Commissioners' Service. The general objectives of Commissioners' services, in addition to protection of the community, are efficient implementation of alternative sanctions, and reducing recidivism rates by successful reintegration, as well as the involvement of local communities in the process of implementing alternative sanctions and post-institutional acceptance of convicts. The aim of this paper is to analyse the current situation and provide examples of good practice, showing the possibility of improving the process of reintegration of prisoners.